Peculiarities of Tax Residency of Individuals in Modern Conditions - BONDARENKO, Iryna M.; BURDIN, Mykhailo Yu.; KAGANOVSKA, Tetyana Ye.; LATKOVSKA, Tamara A.; PONOMARENKO, Yuriy A.; NADOBKO, Serhii V. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The article is devoted to the study of tax residency of an individual in the context of globalization and modern conditions of international cooperation.